A Generic Sacrificial Layer for Wide‐Range Freestanding Oxides with Modulated Magnetic Anisotropy. (12th April 2022) - Peng, Huining; Lu, Nianpeng; Yang, Shuzhen; Lyu, Yingjie; Liu, Zhiwei; Bu, Yifan; Shen, Shengchun; Li, Mingqiang; Li, Zhuolu; Gao, Lei; Lu, Sicheng; Wang, Meng; et al.
Abstract: Freestanding oxide nanomembranes have promising applications because of their novel electronic states and flexible crystalline structures. Several materials have been developed as sacrificial layers to exfoliate thin films from substrates via wet‐etching. However, these materials face great challenges in terms of either complicated crystalline structures or corrosive solutions. Here, a new sacrificial material, SrCoO2.5, is presented, which can be coherently grown with wide‐range strains and crystalline orientations and is also soluble in eco‐friendly solutions such as acetic acid, vinegar, and even carbonated drinks. With SrCoO2.5 as the sacrificial layer, high‐quality freestanding ferromagnetic SrRuO3 membranes are achieved from wide‐range epitaxial strains and different crystalline orientations. By investigating the evolution of the magnetic properties of these samples, it is discovered that epitaxial strain causes a distinct modification of the magnetic anisotropy of (001)pc ‐oriented SrRuO3 samples, while its influence on the (110)pc and (111)pc samples is insignificant. This study not only demonstrates the freestanding SrRuO3 as a promising material for flexible spintronic devices, but also offers a great opportunity to engineer a wide range of strained and oriented complex oxides for novel freestanding electronics using this newly developed sacrificial material. Abstract : Soluble materials used as sacrificial layers are highly desirable for engineering oxide nanomembranes. However, existing materials face challenges of complicated crystalline structures or corrosive solutions. This paper reports that SrCoO2.5, with a simple crystalline structure to adapt to various strains and orientations, is soluble in eco‐friendly solutions, offering an excellent opportunity to explore novel functionalities in freestanding complex oxides.